Does inflation reduce remittance outflows in Saudi Arabia? - Bashier Al-Abdulrazag; Musa Foudeh (Cogent Economics & Finance)
This study examines the potential relationship between inflation and remittance outflows in Saudi Arabia over the period 1971–2019 by applying the autoregressive distributed lag (ARDL) model. As a pioneering study in Saudi Arabia, the paper addresses an important literature gap. The statistical tests reveal the model’s reliability and the existence of a long-run equilibrium among the variables. Moreover, the empirical results show a significant negative impact of inflation has on remittance outflows, and the short-run and long elasticities of remittance with respect to inflation are 0.26% and 0.32% respectively. These results suggest that despite the weak elasticity of remittance outflows to the inflation rate, an increase in general prices would reduce remittance outflows in Saudi Arabia. Moreover, we find that the capital investment indicator has a more significant effect on the volume of remittance outflows. Therefore, policymakers in Saudi Arabia should apply appropriate actions to reduce the outflows of foreign workers by urging private companies to hire more Saudi workers, increasing capital investment and encouraging foreign workers, especially those with high incomes, to invest in Saudi Arabia by facilitating their ownership of financial market shares and real estate units.